The impact of service quality dimensions (SERVQUAL) on customer satisfaction at Tabung Haji Tampin / Nor Asyrani Nekmat and Noor Nadiah Zainal Abidin - Nekmat, Nor Asyrani; Zainal Abidin, Noor Nadiah (Faculty of Business and Management, 2013)
Service in its narrowest nature is intangible which leads to the intricacy of its interpretation. The fact that it needs no conventional method as in the method to assess a product provides it with a rather comprehensive theory. That is where the SERVQUAL model comes to classify and clarify the dimensions of question that need acute attention. This study aims to examine the relationship between service quality dimension and demographic factors on the level of customer satisfaction at Lembaga Tabung Haji Tampin,Negeri Sembilan. Five independent variables have been identified that affect the level of customer satisfaction which are reliability, responsiveness, assurance, empathy and tangible. The dependent variable for this study is customer satisfaction. Literature reviews have been used to support all the dependent and independent variables. One of the most popular methods for measuring the quality of service is to use the development of SERQUAL by Parasuraman, (1998). There were about 150 customers at Tabung Haji Tampin who were selected as the sample of the study. Data were being analyzed using Statistical Package. Result showed that there was a significant relationship between the dimensions of service quality and customer satisfaction. The researchers also came out with some recommendations for the organization in order to increase the level of customer satisfaction at Tabung Haji Tampin.